Root Cause Analysis on Development of Sustainable Fisheries Business in Indonesia - Zulbainarni, Nimmi; Khumaera, Nur Ifra (Jurnal Manajemen dan Agribisnis, 2020)
The development of the capture fisheries sector is significant to improve the national economy, but the development of this sector needs to be regulated to create a sustainable business and ecology of capture fisheries. This study aims to examine the development of the sustainable fisheries sector in Indonesia. This research uses descriptive qualitative method by collecting data from literature studies and focus group discussions (FGD). This study was further analyzed using root cause analysis (RCA). Based on these results, the policy recommendation was obtained to realize sustainable fisheries in Indonesia. This policy recommendation also needs to be supported by government support, such as forming a fishery platform that serves as a mediator for stakeholders so that the policy that is created will positively impact the stakeholders from upstream to downstream. Keywords: capture fisheries, strategy, sustainability, root cause analysis (RCA)